P is for pterodactyl : the worst alphabet book ever : all the letters that misbehave and make words nearly impossible to pronounce - Haldar, Raj; Carpenter, Chris, (Christopher James) (Sourcebooks Jabberwocky, 2018)
Arranged from a to z, presents an entertaining look at the English language, from wacky words to peculiar pronunciations.